Stroke Location and Association With Fatal Cardiac Outcomes: Northern Manhattan Study (NOMAS) - Rincon, Fred (2008)
BACKGROUND AND PURPOSE: Cardiac mortality after stroke is common, and small studies have suggested an association of short-term cardiac mortality with insular location of cerebral infarction. Few population-based studies with long-term follow-up have evaluated the effect of stroke location on the long-term risk of cardiac death or myocardial infarction (MI) after first ischemic stroke. We sought to determine the association between stroke location and cardiac death or MI in a multiethnic community-based cohort. METHODS: The Northern Manhattan Study is a population-based study designed to determine stroke incidence, risk factors, and prognosis in a multiethnic urban population. First ischemic stroke patients age 40 or older were prospectively followed up for cardiac death defined as fatal MI, fatal congestive heart failure, or sudden death/arrhythmia and for nonfatal MI. Primary brain anatomic site was determined by consensus of research neurologists. Hazard ratios (HRs) and 95% CIs were calculated by Cox proportional-hazards models and adjusted for vascular risk factors (age, sex, history of coronary disease, hypertension, diabetes, cholesterol, and smoking), stroke severity, infarct size, and stroke etiology. RESULTS: The study population consisted of 655 patients whose mean age was 69.7 ± 12.7 years; 44.6% were men and 51.3% were Hispanic. During a median follow-up of 4.0 years, 44 patients (6.7%) had fatal cardiac events. Of these, fatal MI occurred in 38.6%, fatal congestive heart failure in 18.2%, and sudden death in 43.2%. In multivariate models, clinical diagnosis of left parietal lobe infarction was associated with cardiac death (adjusted HR = 4.45; 95% CI, 1.83 to 10.83) and cardiac death or MI (adjusted HR = 3.30; 95% CI, 1.45 to 7.51). When analysis of anatomic location was restricted to neuroimaging (computed tomography, magnetic resonance imaging, or both [n = 447]), left parietal lobe infarction was associated with cardiac death (adjusted HR = 3.37; 95% CI, 1.26 to 8.97), and both left (adjusted HR = 3.49; 95% CI, 1.38 to 8.80) and right (adjusted HR = 3.13; 95% CI, 1.04 to 9.45) parietal lobe infarctions were associated with cardiac death or MI. We did not find an association between frontal, temporal, or insular stroke and fatal cardiac events, although the number of purely insular strokes was small. CONCLUSIONS: Parietal lobe infarction is an independent predictor of long-term cardiac death or MI in this population. Further studies are needed to confirm whether parietal lobe infarction is an independent predictor of cardiac events and death. Surveillance for cardiac disease and implementation of cardioprotective therapies may reduce cardiac mortality in patients with parietal stroke.